Motivation towards peacebuilding: the Story of the Young Women Peace Builders in Iraq from Gender Perspective - Hasan, Svana Zana Hasan (Sulaimani Journal for Humanities, 2026)
This study examines the peace activism journey of young women in the context of Iraq. More accurately, the study investigates how the Iraqi young women are motivated to become peace activists. For its theoretical analysis, both feminist theories and motivation theories are applied. Methodologically, the research employed qualitative research techniques by conducting (19) semi-structured interviews with young women peacebuilders from Kirkuk and Nineveh governorates as these two governorates are considered as small Iraq. Through an in-depth analysis of the gathered data, three key themes emerge as pivotal factors propelling women’s engagement in peacebuilding including victimhood, women's representation as a need, and personal benefits. These interconnected motivations together shape these women's journeys toward advocating for peace. By recognizing the significance of these drivers, decision makers, practitioners, and relevant actors can design and develop more targeted strategies to encourage and support the active involvement of young women in peacebuilding efforts.
Keywords: Young women peacebuilders; peacebuilding; motivation; Ethnoreligious group; Iraq